Frontispiece: A General Synthesis of Porous Carbon Nitride Films with Tunable Surface Area and Photophysical Properties. Issue 5 (22nd January 2018) - Peng, Guiming; Xing, Lidan; Barrio, Jesús; Volokh, Michael; Shalom, Menny
Abstract : Photocatalysis In their Communication on page 1186 ff., M. Shalom et al. present a method for growing highly porous and large‐scale carbon nitride (g‐CN) networks on various substrates. The g‐CN films have good photoelectrochemical and photodegradation properties.